La participación ciudadana como un factor determinante de la gobernanza abierta en el GAD municipal del cantón Tosagua. Periodo 2021-2022 - Durán Rodríguez, Carlos Andrés (2023)
The objective of this research is to analyze citizen participation as a determining factor of open governance in the GAD of the Tosagua canton in the period 2021-2022, to guarantee the involvement of the population in issues of public interest, for their achievement. The interview and survey techniques were applied under the Likert scale model, in addition, the inductive, deductive and analytical methods were used that contributed to the processing of the data and information obtained, through field research and investigation. bibliography that supports this study through various sources with high scientific value. In the results obtained, it is highlighted that 40.08% of those surveyed are totally unaware of citizen participation and open government, likewise, 22.90% are indifferent in this regard, while 3.82% of the public is interested in getting involved in issues of public interest in their locality, and 65.27% of the population states that the institution needs to increase the promotion of participatory mechanisms that exist in said entity to take an active part and exercise this right . Based on these identified problems, a set of improvement actions is prepared through a plan to reduce said dilemmas.